Toward a History of New Zealand Legal Education - McLay, Geoff (Victoria University of Wellington Law Review, 1999)
This article briefly discusses the history of New Zealand Legal Education, with a focus on Victoria University of Wellington. The first part of this paper introduces the American and English models of legal education, discussing the different tensions and contexts of each jurisdiction. The second part of the paper introduces the history of legal education in New Zealand. The author discusses New Zealand's departure from the English model (where a degree was not necessary to practise), academics' tradition of writing textbooks in New Zealand, and the influence of the American legal education system. The third part of the paper discusses the impact of Professor John Salmond and Sir Robert Stout at Victoria University of Wellington.